An investigation of the oxidation behaviour of zirconium alloys using isotopic tracers and high resolution SIMS - Yardley, S; Moore, K; Ni, N; Wei, J; Lyon, S; Preuss, M; Lozano-Perez, S; Grovenor, C (2013)
High resolution secondary ion mass spectrometry (SIMS) analysis has been used to study the oxidation mechanisms when commercial low tin ZIRLO™1 and Zircaloy 4 materials are exposed to corroding environments containing both 18O and 2H isotopes. Clear evidence has been shown for different characteristic distributions of 18O before and after the kinetic transitions, and this behaviour has been correlated with the development of porosity in the oxide which allows the corroding medium to penetrate locally to the metal/oxide interface. © 2013 Elsevier B.V. All rights reserved.